Reforming Christian Religious Education: Integrating Spirituality and Critical Reasoning in the Digital Era - Gulo, Rezeki Putra; Tapilaha, Sandra Rosiana (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
This article adopts a qualitative approach, utilizing both library research and phenomenology. It aims to explore new approaches in Christian religious education that integrate spirituality with critical reasoning, addressing the challenges posed by the current digital era. The core issue examined is how to equip students with critical reasoning skills while simultaneously deepening their faith and spirituality in the context of digital technology, highlighting both the challenges and opportunities this presents. By reviewing a range of relevant literature, this research presents best practices for addressing the pedagogical needs of students in the digital era. Its originality lies in a holistic approach that integrates spiritual development with critical reasoning in the learning process, offering a new model for shaping Christian thinkers who are both critically minded and deeply committed to their faith in an era of rapid technological advancement. The research reveals that integrating digital technology into Christian religious education greatly improves student engagement in the learning process. Moreover, combining critical reasoning with spiritual development enables students to gain a deeper and more relevant understanding of Christian values in the context of the digital era.